Analytical Study for the Charge-Transfer Complexes of Pregabalin - Hesham Salem (E-Journal of Chemistry)
Studies were carried out, for the first time, to investigate the charge-transfer reactions of Pregabalin (PRE) as n-electron donor with various π-acceptors: 7,7,8,8-tetracyanoquinodimethane (TCNQ), 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), 2,5-dichloro-3,6-dihydroxy-1,4-benzoquinone (chloranilic acid, pCA), tetracyanoethylene (TCNE) and 2,3,5,6-tetrachloro-1,4-benzoquinone (chloranil). Different colored charge-transfer complexes and radical anions were obtained. Different variables affecting the reactions were studied and optimized. The formations of the colored complexes were utilized in the development of simple, rapid and accurate spectrophotometric methods for the analysis of PRE in pure form as well as in its pharmaceutical preparation. Under the optimum reaction conditions, linear relationships with good correlation coefficients (0.9995-0.9999) were found between the absorbance and the concentrations of PRE in the range of 8-400 µg mL-1. The limits of assays detection ranged from 0.60 to 8.11 µg mL-1. No interference could be observed from the additives commonly present in the capsules. The methods were successfully applied to the analysis of capsules that contain PRE, with good accuracy and precision; the recovery percentages ranged from 100.19±0.83 to 100.50±0.53. The results were compared favorably with the reported method.